STRUCTURE, BIOMASS AND CARBON STOCKS CHARACTERISTICS OF ACACIA HYBRID FORESTS IN HAM YEN, TUYEN QUANG - Thi Bich Phuong, Nguyen (Journal of Forestry Science and Technology, 2019)
Research on biomass and carbon stocks is very meaningful for managing and minimizing negative effects of climate change and global warming on people’s lives. The study collected and analyzed data from plots for Acacia hybrid forests at two different age levels: 2 years and 6 years old in Ham Yen, Tuyen Quang. The analytical results showed that density at age 6 was lower than age 2. The diameter and height frequency distributions were well simulated by Weibull distribution. The distributions at the age 2 followed the Weibull distribution better than the age 6. Age 2, Power function is the best function, while at age 6, Cubic function is the best function to describe the correlation between diameter and height. The total amount of fresh biomass of Acacia hybrid is about 24.59 (ton/ha) for ages 2 and 89.92 (ton/ha) for age 6. Biomass concentrated mainly on the tree layer, then on the vegetation floor and litter layer. Dry biomass is quite similar to the fresh biomass distribution. With a forest density of 1540 plant/ha, the amount of CO2 absorbed by age 2 was 5.13 (ton/ha). The amount of CO2 absorbed by age 6 was 30.73 ton/ha with a forest density of 1240 tree/ha. The average amount of underground carbon at sampling point 1 was 29.51 (ton/ha), lower than the average carbon at the sampling point 2 was 30.56 (ton/ha). The amount of carbon decreases gradually from the surface layer to the 10 - 20 cm layer and finally to the 20 - 30 cm layer.